Translocations Disrupting PHF21A in the Potocki-Shaffer-Syndrome Region Are Associated with Intellectual Disability and Craniofacial Anomalies - Kim, Hyung-Goo (Elsevier, 2012)
Potocki-Shaffer syndrome (PSS) is a contiguous gene disorder due to the interstitial deletion of band p11.2 of chromosome 11 and is characterized by multiple exostoses, parietal foramina, intellectual disability (ID), and craniofacial anomalies (CFAs). Despite the identification of individual genes responsible for multiple exostoses and parietal foramina in PSS, the identity of the gene(s) associated with the ID and CFA phenotypes has remained elusive. Through characterization of independent subjects with balanced translocations and supportive comparative deletion mapping of PSS subjects, we have uncovered evidence that the ID and CFA phenotypes are both caused by haploinsufficiency of a single gene, PHF21A, at 11p11.2. PHF21A encodes a plant homeodomain finger protein whose murine and zebrafish orthologs are both expressed in a manner consistent with a function in neurofacial and craniofacial development, and suppression of the latter led to both craniofacial abnormalities and neuronal apoptosis. Along with lysine-specific demethylase 1 (LSD1), PHF21A, also known as BHC80, is a component of the BRAF-histone deacetylase complex that represses target-gene transcription. In lymphoblastoid cell lines from two translocation subjects in whom PHF21A was directly disrupted by the respective breakpoints, we observed derepression of the neuronal gene SCN3A and reduced LSD1 occupancy at the SCN3A promoter, supporting a direct functional consequence of PHF21A haploinsufficiency on transcriptional regulation. Our finding that disruption of PHF21A by translocations in the PSS region is associated with ID adds to the growing list of ID-associated genes that emphasize the critical role of transcriptional regulation and chromatin remodeling in normal brain development and cognitive function.